Online Learning-Related Visual Function Impairment During and After the COVID-19 Pandemic - Fan, Qian; Wang, Hongxia; Kong, Wenjun; Zhang, Wei; Li, Zhouyue; Wang, Yan (Frontiers in Public Health, 2021)
To review the consequences of increased online learning, precipitated by the COVID-19, on visual function, and the methods for preventing the associated visual impairment. The recent finding implies that a higher incidence of myopia may be observed during the pandemic than that before. Online learning precipitated by COVID-19 is likely to increase the global burden of visual function impairment. This review highlights useful measures to prevent online learning-related visual function impairments - desktop illumination of no less than 300 lx; online learning time for primary- and middle-school students of no more than 20-30 minutes per session; daily video time for preschool children not exceeding 1 hour, and for school-age children and adolescents not exceeding 2 hours; after every 30-40 minutes of online learning, moving eyes away from the screen or closed for 10 minutes; engaging in outdoor activities for ≥ 2 hours a day; suitable screen and learning environment settings and correct postures for reading and writing; sufficient sleep and proper nutrition. Preventing online learning-related visual impairment during and after this unprecedented pandemic will facilitate future ophthalmic practice.